Discourse on Inequality - Rousseau, Jean-Jacques.; Cranston, maurice (tr.) (London, 1984)
A fascinating examination of the relationship between civilization and inequality from one of history$1 (Bs greatest minds. The first man to erect a fence around a piece of land and declare it his own founded civil society$1 (Band doomed mankind to millennia of war and famine. The dawn of modern civilization, argues Jean-Jacques Rousseau in this essential treatise on human nature, was also the beginning of inequality. One of the great thinkers of the Enlightenment, Rousseau based his work in compassion for his fellow man. The great crime of despotism, he believed, was the raising of the cruel above the weak. In this landmark text, he spells out the antidote for man$1 (Bs ills: a compassionate revolution to pull up the fences and restore the balance of mankind. This ebook has been professionally proofread to ensure accuracy and readability on all devices.s
Keywords: Political theory-Rousseau